Investigating the effect of Ayatollah Javadi Amoli's theory of "human-to-human interpretation" on the strategies for achieving spiritual health - Omid Ahanchi; Yahya Sabbaghchi (اخلاق وحیانی)
Humans in general and thinkers in particular have always sought to increase the quality of life and achieve health in all its dimensions. For more than three decades, spiritual health has been one of the dimensions of health in the World Health Organization, but it still has hidden angles that have made it difficult for human societies to achieve. Due to the great impact of the constraints of human societies on spiritual health, it is necessary for each society to analyze this concept according to its requirements in order to achieve tangible and workable results. Therefore, the present study has been organized with the aim of investigating the effects of accepting the theory of "human-to-human interpretation" on the strategies for achieving spiritual health. The research method is descriptive-analytical. In terms of purpose, the present study is an applied research, because the purpose of doing so is to develop applied knowledge about ways to achieve spiritual health. The findings of the research indicate that according to this theory and also according to accepting the definition of man as "the alive theosopher", the way to achieve spiritual health is to return the allegories of man to the decisive of his existence (divine nature) and also to follow a perfect human being and finally to realize the "monotheistic look”. According to the works of Ayatollah Javadi Amoli, it can be inferred that the monotheistic view is the source of four important principles: full attention to the position of the divine vicegerent, viewing existence as the sign of God, seeing creation of man and the world as purposeful and finally achieving divine devotion and understanding the philosophy of human life. According to these four principles, strategies for achieving spiritual health from the perspective of Ayatollah Javadi Amoli can be achieved.